Value coordinates of students resilience under martial law in Ukraine. - Virna, Zhanna P.; Ivanashko, Oksana; Lysenko, Svitlana (The State University of Western Paraná, 2024)
The theoretical substantiation of the problem actualizes the need to study it in the context of the psychological alliance of manifestation of value orientation and resilience, which is a powerful personal resource for survival under martial law.A program of empirical research has been developed, as well as a set of methods for mathematical processing of results, made it possible to determine the differences in the main dimensions of value orientations.The students with a high level of resilience are dominated by the value dimensions of "openness to change" and "self-overcoming", which are framed in psychological portraits of "controlled independence" and "altruistic activity"; Their psychological profileon the grounds of prosocial responsibility, altruism, humanistic orientation comprehensively explicates the intra-oriented life attitude of the value system. For students with a low level of resilience, the dominance of the basic dimension of value orientations "self-assertion" determines the psychological portrait of the "power reputation"; Their psychological profile on the signs of a pronounced desire to satisfy their own interests and preserve a reputational image is an externally oriented life attitude. The results obtained can be successfully used by psychologists in the education system to monitor the psychological recovery and post-traumatic growth of students
Keywords: Resilience; Value orientations; Martial law